2020
DOI: 10.14814/phy2.14434
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietin and a hypoxia‐inducible factor prolyl hydroxylase inhibitor (HIF‐PHDi) lowers FGF23 in a model of chronic kidney disease (CKD)

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 31 publications
3
39
0
Order By: Relevance
“…A recent paper, however, showed that EPO and HIF-PHI treatment of anemic mice with CKD resulted in suppressed FGF23. This study suggested that under conditions of anemia, as opposed to mice with normal iron homeostasis, rescuing iron utilization during CKD may be a more potent suppressor of FGF23 than EPO and HIF-PHIs are stimulators ( 70 ). Although EPO and HIF-PHI can induce FGF23, further studies are required to delineate the mechanisms directing these components on osteocytic FGF23 production.…”
Section: Fgf23 Production and Cleavage In Osteocytesmentioning
confidence: 98%
“…A recent paper, however, showed that EPO and HIF-PHI treatment of anemic mice with CKD resulted in suppressed FGF23. This study suggested that under conditions of anemia, as opposed to mice with normal iron homeostasis, rescuing iron utilization during CKD may be a more potent suppressor of FGF23 than EPO and HIF-PHIs are stimulators ( 70 ). Although EPO and HIF-PHI can induce FGF23, further studies are required to delineate the mechanisms directing these components on osteocytic FGF23 production.…”
Section: Fgf23 Production and Cleavage In Osteocytesmentioning
confidence: 98%
“…The studies which juxtaposed the effects of roxadustat with those of erythropoietin [ 22 , 25 , 27 , 29 , 30 ] or darbapoietin [ 28 ], showed that, regarding changes in hemoglobin levels, the effects of roxadustat were not worse, while being usually better than the effects of erythropoietin…”
Section: Discussionmentioning
confidence: 99%
“…Phase 3 clinical studies of roxadustat were started in 2014. There are currently more than 15 phase 3 clinical trials underway with a target enrollment of about 10,000 patients worldwide, studying the safety, efficacy, and long-term effects of roxadustat in CKD patients, including non-dialysis-dependent [ 23 , 24 , 25 , 26 ], hemodialysis-dependent [ 22 , 25 , 27 , 28 , 29 ] and peritoneal dialysis-dependent subjects [ 25 , 30 ]. See below for a few presented examples.…”
Section: Roxadustat—phase 3 Studiesmentioning
confidence: 99%
“…They reported that, upon treatment with HIF-PHD inhibitor FG-4592, iFGF-23 serum levels dropped remarkably. As a result, deficiency of iron metabolism stabilized through decreased liver ferritin, Bmp6, and hepcidin mRNAs [165]. Taken together, FGF-23 constitutes an important regulator of erythropoiesis and bone homeostasis.…”
Section: Hif-epo-fgf23 Axis: Phd2/hif Inhibitionmentioning
confidence: 99%